Study of borehole stability of volcanic rock formation with the influence of multiple factors - Mingming Zhang; Jinglin Wen; Zhiming Xu; Zhiwei Xu; Jiang Feng; Xingdong Zhao (Journal of Petroleum Exploration and Production Technology)
Abstract Borehole instability in igneous rock formation has attracted more and more attention in recent ten years. In order to understand the mechanism of wellbore instability in igneous formation, a borehole stability model is established by applying the thermal, seepage and stress coupling model combined with a true triaxial rock strength criterion, which can reveal evolution of borehole collapse pressure with time. The effect of drilling cycle on borehole collapse pressure considering the coupling effects of temperature, seepage, and stress is quantitatively analyzed. Results show that, compared with only considering the effect of stress, wellbore collapse pressure increases with the coupling effect of temperature, seepage, and stress. Meanwhile, the stability of wellbore can be enhanced by reducing drilling fluid temperature; with the increase of formation porosity, the borehole collapse pressure increases rapidly, and then remains unchanged or decreases; while with the increase of formation permeability, borehole collapse pressure decreases rapidly, i.e. the shear failure of wellbore is mitigated. Besides, compared with vertical well, the horizontal well is more sensitive to the change of rock permeability. The investigation of drilling cycle shows that, the borehole collapse pressure increased sharply when the formation was drilled instantaneously. However, the subsequent growth trend slows down, which suggests that during the early stages of drilling operation, it is advisable to appropriately increase the mud weight to enhance the wellbore’s support capability by the bottomhole pressure. The research findings can enhance the understanding of the instability mechanism of igneous rock formations and reduce the risk of wellbore instability in igneous rock formations.